Anisotropy and non-linearity of absorption of an intensive IR light by free electrons in germanium - Vasetskii, V.M.; Ignatenko, V.A.; Poroshin, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The anisotropy and non-linearity of absorption of the intensive CO₂ laser radiation by free electrons in germanium has been found. The effect is caused by redistribution of electrons among equivalent valleys occurring due to non-equal heating electrons in the valleys which have different orientation in regard to the electric field of the light wave.